Road Traffic Crashes - Cultural nuances & impacts (a concept note) - Ramos, M. (Working Group 5 - UNRSC 24th Meeting, Bangkok, 2017)
Although regionally and nationally varied, road traffic systems worldwide enjoy a high degree of recognized commonalities that lead to a high level of standartization in conceptions and responses to the risks and traumas involved: vehicles, road environments and users are similar to a large degree; the devastating physical and psychological consequences of road crashes know no borders. Medical response systems and enforcement systems may tend to be harmonized but they coexist with competing informal healing specialists and with customary authorities, whose legitimacy they generally fail to acknowledge. The same must be said of the immense differences in judicial systems, and particular when different judicial systems may apply in the same country or locality. Knowing how guilt, blame, victimization, responsability are tackled in different countries and in diferent religious and ethnic groupings is of utmost importance but there is a visible lack of information in this area. Finally, there is a blatant absence of knowledge in what may be the role of religion and culture in the way direct and indirect victims of road crashes are rehabilitated and reintegrated in their communities, and how remembrance of the dead is pursued, in different countries and localities. Language differences, cultural traditions and ideological-religious adherences should not be taken as embarassing and disposable byproducts of the way road traffic systems operate. They are important drivers of their conceptualization, and so, improvement in the risks and traumas they produce may be better fine-tuned if those factors are better understood and taken into consideration when conceiving plans and producing solutions.